PENYELESAIAN TINDAK PIDANA DISKRIMINASI ETNIS DI LUAR PENGADILAN MELALUI LEMBAGA ADAT MELAYU RIAU - Putra, Raka Prasetya; Erdianto, Erdianto; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In formal legal conduct contrary to criminal law, including discrimination, acts of racial and ethnic discrimination are prohibited in Article 4 (b) (2) of Law No. 40 of 2008 on the Elimination of Racial and Ethnic Discrimination, which reads : 'Shows hatred or hatred towards people because of racial and ethnic differences in the form of: (2): Speech, express or say certain words in a public place or other place that can be heard by others. In the settlement of criminal offenses, especially in minor criminal law, two choices are made to solve criminal law problems, namely litigating or not litigating. peace consultation mechanism (no litigation) In indigenous peoples, the case can be resolved out of court as long as the issue is a minor criminal case. Among the cases that arose around disputes as well as insults between ethnic groups between Malays and Batak tribes, this subsequently caused commotion, involving insults between racial and ethnic groups leading to disputes that were not in accordance with existing laws . The wording of the problems in this dissertation research is, first, how the legal perspective is related to the settlement of ethnic discrimination crime out of court. second, how the law can be enforced in the settlement of ethnic discrimination crimes through the Riau Malay Customary Institution From the results of research based on two problem formulations, it can be concluded: First, this settlement is resolved out of court through common law mechanisms to bring about peace, brotherhood and restoration of relations in society, in positive law the common law system is not regulated but is recognized and has legal provisions. that is at the level of positive law because this customary law has existed for generations and is used in customary law communities. Second, settlement out of court through the customary courts, settlement in this customary institution is not regulated in the positive legal system in Indonesia but has a recognized position in the Indonesian legal system, because the State recognizes and respects the position of customary law. Keywords: Racial and ethnic- discrimination-Indigenous Institutions